Pemanfaatan Kecerdasan Buatan (Artificial Intelligence) dalam Proses Pembelajaran: Refleksi Sosiologis Mahasiswa Aktif Pendidikan Sosiologi Untirta - Septiani, Dini; Setiawan, Rizki (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study explores the meaning and use of artificial intelligence (AI) by Sociology Education students at Universitas Sultan Ageng Tirtayasa. Using a phenomenological qualitative approach, data were collected through in-depth interviews. The findings indicate that AI serves as a learning aid facilitating understanding and idea organization, but it does not replace critical thinking or social interaction. Sociologically, AI influences interactions, creates digital literacy stratification, social structure, and shapes a hybrid academic culture that is efficient yet potentially dependency-inducing.